Sticking to cellulose: exploiting Arabidopsis seed coat mucilage to understand cellulose biosynthesis and cell wall polysaccharide interactions. Issue 3 (13th February 2017) - Griffiths, Jonathan S.; North, Helen M.
Summary: The cell wall defines the shape of cells and ultimately plant architecture. It provides mechanical resistance to osmotic pressure while still being malleable and allowing cells to grow and divide. These properties are determined by the different components of the wall and the interactions between them. The major components of the cell wall are the polysaccharides cellulose, hemicellulose and pectin. Cellulose biosynthesis has been extensively studied in Arabidopsis hypocotyls, and more recently in the mucilage‐producing epidermal cells of the seed coat. The latter has emerged as an excellent system to study cellulose biosynthesis and the interactions between cellulose and other cell wall polymers. Here we review some of the major advances in our understanding of cellulose biosynthesis in the seed coat, and how mucilage has aided our understanding of the interactions between cellulose and other cell wall components required for wall cohesion. Recently, 10 genes involved in cellulose or hemicellulose biosynthesis in mucilage have been identified. These discoveries have helped to demonstrate that xylan side‐chains on rhamnogalacturonan I act to link this pectin directly to cellulose. We also examine other factors that, either directly or indirectly, influence cellulose organization or crystallization in mucilage.